PENANAMAN NILAI – NILAI PENDIDIKAN AGAMA ISLAM PADA ANAK USIA DINI - Fauzan Ananta; Wahyu Rizky (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
Islamic Religious Education (PAI) plays an important role in shaping the character and morals of the younger generation, especially in early childhood. This education includes the teaching of the values of aqidah, worship, and morals, which aims to cultivate strong Islamic character from an early age, as well as equip children with the ability to face challenges in the modern era, research shows that the role of educators and parents is very significant in this process, where their contribution in teaching and applying religious values through various methods such as memorization of the Qur'an, Storytelling, daily routines, and the integration of religious values in daily activities are key factors. The method in this study is a literature study by analyzing as a source of good from books, journals and various other reference sources. The results of this study are about the challenges in the implementation of religious values in early childhood. Covering media influence